Systematic Literature Review: The Role of Internal Auditor Performance in Non-Profit Organizations - Ramdani, Safier; Widyastuti, Tri; Darmansyah, Darmansyah; Rito, Rito (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this research is to study the role of internal auditors in improving the performance of non-profit organizations. To achieve this goal, this research uses a systematic literature review method. In non-profit organizations, performance is often measured by looking at the social impact and sustainability of programs as well as financial gains. Internal auditors are very important to ensure that the organization operates well and complies with regulations and ethics. This research identifies various components that influence the performance of internal auditors; these include management support, independence, and competence. Additionally, the lack of resources and the complexity of measuring non-financial performance are specific issues faced by internal auditors in non-profit environments, which are the focus of this research. The results of this literature review indicate that internal auditors can improve the performance of non-profit organizations by providing honest assessments and valuable recommendations. According to this research, non-profit organizations should strengthen their internal audit functions and ensure that internal auditors are continuously trained to address emerging issues. These findings are expected to help academics and practitioners understand how to maximize the role of internal auditors in the non-profit sector.